Estimation of Resilience in University Students - Meza, Anicia Katherine Tarazona; Aguayo, Marina Dalila Zambrano; Cevallos, Miguel Giancarlo Ormaza; Zambrano, Patricio FabiÃƒÂ¡n Rezabala (International Research Journal of Management, IT & Social Sciences, 2018)
The objective of the work is to estimate the resilience level of university students for future resilience interventions. The paper presents a conceptual analysis of the term resilience, based on the criteria of contemporary authors framed in two generations. The methods and techniques used in the work are exposed, where two tools for measuring resilience are highlighted. The importance of the study of resilience in the university environment is discussed and the statistical and graphical results related to the application of the aforementioned instruments are shown in terms of measuring the resilience level in the university students of seven faculties of the Technical University of ManabÃ.